Structural, Electronic Properties, Hydrogen Bonding Analyses, and Biological Activity of Two Multiple Myeloma Drugs: Lenalidomide and Pomalidomide. (7th August 2016) - Srivastava, Ambrish Kumar; Pandey, Anoop Kumar; Pandey, Saurabh; Misra, Neeraj
Abstract : In this article, we made a comparative study of two multiple myeloma drugs: lenalidomide and pomalidomide. We calculated and discussed their geometries at DFT/B3LYP method. Intra-molecular hydrogen bonding in these molecules is confirmed and characterized by QTAIM calculations. Electronic parameters along with HOMO-LUMO and MESP surfaces are calculated in order to compare their chemical reactivity. The effect of structure and bonding on electronic properties and biological activities is discussed and it is established that pomalidomide is more biologically active than lenalidomide. The phenyl ring of these molecules show teratogenic effects, making a possibility of finding another new class of drugs.